If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12 = 7a + -5 Reorder the terms: -12 = -5 + 7a Solving -12 = -5 + 7a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7a' to each side of the equation. -12 + -7a = -5 + 7a + -7a Combine like terms: 7a + -7a = 0 -12 + -7a = -5 + 0 -12 + -7a = -5 Add '12' to each side of the equation. -12 + 12 + -7a = -5 + 12 Combine like terms: -12 + 12 = 0 0 + -7a = -5 + 12 -7a = -5 + 12 Combine like terms: -5 + 12 = 7 -7a = 7 Divide each side by '-7'. a = -1 Simplifying a = -1
| [-6x]+18=[-6] | | -4+7=-10x+37 | | 2q=2p-4 | | 16y-65=0 | | 5x+5=[-10] | | 7-x=40x | | 20x^3-40=0 | | 2s-2s+2s+2s=4 | | -7v+8=-8v | | 150-221/2 | | 12*x^2-202.8*x+623.7=0 | | 3(s+1)-w=1 | | 32-43x=-140 | | 2y-(0)=6 | | D=a+3 | | 98b^2=0 | | h-16=3 | | 8s+20t= | | Xx-12=4 | | B=4g | | -2-3p=17 | | t(n)=5n+8 | | p/-3=-7 | | s*4+37=121 | | 7m+5m-2m-6m= | | F=2g+4 | | 3(2a+b)+2(a+3b)= | | 8b+(-11b)+16b-7b-9b=18 | | 13x=29 | | 108=2*n | | 8-4s=1s*13 | | 5q+q+q-3q-3q+1=18 |